Albendazole induces oxidative stress and DNA damage in the parasitic protozoan Giardia duodenalis - Martínez-Espinosa, Rodrigo; Argüello-García, Raúl; Saavedra, Emma; Ortega-Pierres, Guadalupe (Frontiers in Microbiology, 2015)
The control of Giardia duodenalis infections is carried out mainly by drugs, among these albendazole (ABZ) is commonly used. Although the cytotoxic effect of ABZ usually involves binding to β-tubulin, it has been suggested that oxidative stress may also play a role in its parasiticidal mechanism. In this work the effect of ABZ in Giardia clones that are susceptible or resistant to different concentrations (1.35, 8 and 250 μM) of this drug was analyzed. Reactive oxygen species (ROS) were induced by ABZ in susceptible clones and this was associated with a decrease in growth that was alleviated by cysteine supplementation. Remarkably, ABZ-resistant clones exhibited partial cross-resistance to H2O2, whereas a Giardia H2O2-resistant strain can grow in the presence of ABZ. Lipid oxidation and protein carbonylation in ABZ-treated parasites did not show significant differences as compared to untreated parasites; however ABZ induced the formation of 8OHdG adducts and DNA degradation, indicating nucleic acid oxidative damage. This was supported by observations of histone H2AX phosphorylation in ABZ-susceptible trophozoites treated with 250 μM ABZ. Flow cytometry analysis showed that ABZ partially arrested cell cycle in drug-susceptible clones at G2/M phase at the expense of cells in G1 phase. Also, ABZ treatment resulted in phosphatidylserine exposure on the parasite surface, an event related to apoptosis. All together these data suggest that ROS induced by ABZ affect Giardia genetic material through oxidative stress mechanisms and subsequent induction of apoptotic-like events.